Local Participation in the Development of Klayar Beach Tourism in Pacitan Regency - M. Husni Tamrin; Wildan Taufik Raharja (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the process of local participation in the development of Klayar Beach tourism in Pacitan Regency by looking at the compatibility between the dynamics of increasing tourists and the participation of local communities in development. From this, it is known to what extent the contribution and participation of local communities in tourism development participation efforts. The implication of this research is an explanation related to the results of the analysis of the gaps in the stages of participation by the local community as managers. The research method is descriptive analytic by using triangulation as a data analysis technique. The results show that local participation runs in all stages of the development of the Klayar Beach tourist area from the beginning, tourism issues, planning, implementation and governance, to monitoring and evaluation. The lack of local participation lies in participation in terms of anticipating tourist arrivals at certain times and moments, in which case the local community as managers experience limitations in terms of capacity. To overcome this, the researcher suggests that efforts be made to increase local capacity both in terms of quality and quantity so that local participation efforts can run optimally in the development and sustainability process, and be able to overcome unexpected problems through the role of participation. This effort also refers to the opinion of several experts who state that local participation is one of the main keys in developing the tourism sector